Transesterification reaction time impacts on oxidation stability and acid number of biodiesel production from waste cooking oil - Randa Pratama; Muhammad Idris; Zakir Husin; Zainal Arif; Iskandar Yakoeb; Supriadi (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
The scarcity of fossil fuels, environmental concerns, and the sharp rise in fossil fuel prices have driven scientists to search for alternative fuels. The characteristics of biodiesel have made the quest for high-quality biodiesel production particularly appealing. The use of waste cooking oil is a key component in reducing biodiesel production costs by 60-90%. Researchers have employed various types of transesterification reactions with both homogeneous and heterogeneous catalysts for biodiesel production; in this study, a 0.5% NaOH catalyst is used. The objectives of this study are to produce biodiesel fuel based on waste cooking oil, evaluate the impact of reaction time variation on the oxidation value and acid value of biodiesel produced from waste cooking oil, and statistically test the effects of reaction time on the oxidation value and acid value of biodiesel produced from waste cooking oil using analysis of variance (ANOVA). The optimum yield was obtained at a reaction time of 90 minutes, achieving 97%. The results for acid number and oxidation value for various reaction times complied with ASTM, EN, and SNI standards. Linear regression analysis of ANOVA for the acid number concluded that the P-value t3 is 0.399, which is greater than Alpha = 0.05, indicating that the variation in reaction time does not have a significant effect on the acid number. Linear regression analysis of ANOVA for the oxidation number concluded that the P-value t3 is less than Alpha (0.047 < 0.05), indicating that reaction time has a significant effect on the oxidation number.